Association between estrogen receptora gene (ESR1) PvuII (T/C) and XbaI (A/G) polymorphisms and premature ovarian failure risk: evidence from a meta-analysis - He, Meirong; Shu, Jingcheng; Huang, Xing; Tang, Hui (Journal of assisted reproduction and genetics, 2015)
Background and aims Genetic factors are important in the pathogenesis of Premature ovarian failure (POF). Notably, estrogen receptor-a ( ESR1 ) has been suggested as a possible candidate gene for POF; however, published studies of ESR1 gene polymorphisms have been hampered by small sample sizes and inconclusive or ambiguous results. The aim of this meta analysis is to investigate the associations between two novel common ESR1 polymorphisms (intron 1 polymorphisms PvuII-rs2234693: T.C and XbaI-rs9340799: A.G) and POF. Methods A comprehensive search was conducted to identify all studies on the association of ESR1 gene polymorphisms with POF up to August 2014. Pooled odds ratio (OR) and corresponding 95 % confidence interval (CI) were calculated using fixed-or random-effects model in the meta-analysis. Results Three studies covering 1396 subjects were identified. Pooled data showed significant association between ESR1 gene PvuII polymorphism and risk of POF: [allele model: Cvs. T, OR = 0.735, 95%CI: 0.624 ~ 0.865, p = 0.001; co-dominant models: CCvs.TT, OR = 0.540, 95%CI: 0.382 ~ 0.764, p = 0.001, CTvs.TT, OR = 0.735, 95%CI: 0.555 ~ 0.972, p = 0.031; dominant model: CT + CCvs.TT, OR = 0.618, 95%CI: 0.396 ~ 0.966, p = 0.035; recessive model: CCvs.TT + CT, OR = 0.659, 95%CI: 0.502 ~ 0.864, p = 0.003]. Subgroup analyses showed a significant association in all models in Asian population, but no significant association in any model in European population. For the XbaI polymorphism, overall, no significant association was observed under any genetic models. However, under dominant model, ESR1 gene XbaI polymorphism is significantly association with risk of POF in Asian population. Conclusion The present meta-analysis suggests that ESR1 gene PvuII polymorphism is significantly associated with an increased risk of POF. And ESR1 gene XbaI polymorphism is not association with risk of POF overall. However, under dominant model, ESR1 gene XbaI polymorphism is significantly association with risk of POF in Asian population. Further large and well-designed studies are needed to confirm the association.